Mampukah Citra Merek, Fasilitas dan Kepercayaan Meningkatkan Kepuasan Pengunjung Taman Hewan Kota Pematangsiantar - Onita Sari Sinaga; Debi Eka Putri; Astri Rumondang Banjarnahor; Fitria Halim; Acai Sudirman (Inovbiz: Jurnal Inovasi Bisnis, 2020)
The manifestation of customer satisfaction can be seen from the pattern of consumer behavior on a product of goods and services. Many factors can influence consumer behavior, including product quality, price offered, promotion mechanism presented, ease of seeking purchase places, and many other factors that can influence it. This study aimed to examine the effect of brand image, facilities, and consumer trust on customer satisfaction, both partially and simultaneously. This study used a quantitative method. The data were obtained from the distribution of questionnaires to 321 respondents who were the sample of the population studied. The data analysis technique used to test the hypothesis was multiple regression analysis which included the t-test, F-test, and the coefficient of determination test. The results of the study with the t-test model explained that: the brand image had an effect on customer satisfaction, facilities had an effect on customer satisfaction, consumer trust had an effect on customer satisfaction. Furthermore, the results of the simultaneous test (F-test) stated that brand image, facilities, and consumer trust had a significant effect on customer satisfaction. The coefficient of determination test explained that customer satisfaction n was influenced by brand image, facilities, and consumer trust by 71.6% and the remaining 28.4% was influenced by other factors not examined in this study.